2020
DOI: 10.1155/2020/8853444
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Circulation and Astrocytes Contribute to the MSC-Mediated Increase in IGF-1 Levels in the Infarct Cortex in a dMCAO Rat Model

Abstract: Background and Purpose. Previously, we found that insulin-like growth factor-1 (IGF-1) levels in the infarct cortex in the acute phase of distal middle cerebral artery occlusion (dMCAO) rats are increased by intravenous infusion of allogeneic mesenchymal stem/stromal cells (MSCs). CD68+ microglia and NeuN+ neurons are part, but not all, of the sources of IGF-1. The present study is aimed at exploring the respective contributions of brain endogenous Iba-1+ microglia, GFAP+ astrocytes, infiltrated neutrophils, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We observed that EA's reduction of microglial proliferation and its enhancement of M2 markers were impeded by co-administration of the IGF1R inhibitor PPP. IGF-1 and its receptor IGF1R are found in a wide array of cell types in the central nervous system, including neurons 59 , 60 , astrocytes 60 , 61 , and macrophage/microglia 60 , 62 . IGF-1 is recognized for its anti-inflammatory role in the brain, which it accomplishes by managing microglial inflammation 63 , the reduction of pro-inflammatory factors 24 , 64 , and modulation of astrocytic phagocytosis 65 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that EA's reduction of microglial proliferation and its enhancement of M2 markers were impeded by co-administration of the IGF1R inhibitor PPP. IGF-1 and its receptor IGF1R are found in a wide array of cell types in the central nervous system, including neurons 59 , 60 , astrocytes 60 , 61 , and macrophage/microglia 60 , 62 . IGF-1 is recognized for its anti-inflammatory role in the brain, which it accomplishes by managing microglial inflammation 63 , the reduction of pro-inflammatory factors 24 , 64 , and modulation of astrocytic phagocytosis 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this increase in IGF-1 expression and secretion with MSC transplant is accompanied by significant improvements in behavioral function. 144,145 The causal role of MSCderived IGF-1 as a neuroprotector is supported by recent findings that overexpression of IGF-1 in MSCs transplanted into a rodent model of spinal cord injury showed a significant reduction in inflammation, oxidative stress, and neurological deficits. 144,145 There are limited studies on IGF-1 as a modulator of stem cell therapies in humans, however, a recent study in a small cohort of chronic stroke patients disclosed that exogenous IGF-1 was used to prep neural stem cells for effective transplant.…”
Section: Potential Roles Of Igf-1 In Astrocytes Following a Strokementioning
confidence: 92%
“…144,145 The causal role of MSCderived IGF-1 as a neuroprotector is supported by recent findings that overexpression of IGF-1 in MSCs transplanted into a rodent model of spinal cord injury showed a significant reduction in inflammation, oxidative stress, and neurological deficits. 144,145 There are limited studies on IGF-1 as a modulator of stem cell therapies in humans, however, a recent study in a small cohort of chronic stroke patients disclosed that exogenous IGF-1 was used to prep neural stem cells for effective transplant. 146 Additional work in this area is needed to understand whether supplemental IGF-1 can support effective stem cell therapies for individuals in recovery from stroke.…”
Section: Potential Roles Of Igf-1 In Astrocytes Following a Strokementioning
confidence: 92%
“…New findings suggest that matrix metalloproteinases receptor cleavage has a notable role in the ineffective IGF-1 signaling in hypertension and might be significant for peripheral vascular resistance ( 19 ). Interestingly, manipulation of IGF-1 levels in the peripheral circulation and its increased levels in the brain could be used to recover early manifestations of cerebral artery occlusion ( 78 ). Regarding human studies, IGF-1 infusion reduced peripheral resistance in patients with chronic heart failure, suggesting its acute impact on the CV system ( 79 ).…”
Section: Igf-1 Systemmentioning
confidence: 99%